Car User Taxes, Quality Characteristics and Fuel Efficiency: Household Behavior and Market Adjustment - Bruno de Borger; Jan Rouwendal (Tinbergen Institute, 2012)
We study the impact of fuel taxes and kilometer taxes on households' choices of vehicle quality, on their demand for kilometers driven, and on fuel consumption. Moreover, embedding this information in a model of the car market, we analyze the implications of these taxes for the opportunity costs of owning cars of different quality. Higher quality raises the fixed cost of car ownership, but it may raise (engine size, acceleration speed, etc.) or reduce (fuel technology, etc.) the variable user cost. Our results show that kilometer charges and fuel taxes have very different implications. For example, a higher fuel tax raises household demand for more fuel efficient cars, provided that the demand for car use is inelastic; it reduces the demand for characteristics that raise variable user costs. Surprisingly, however, a kilometer tax unambiguously reduces the demand for more fuel efficient cars. Incorporating price adjustments at the market level, we find that fuel taxes raise the marginal fixed opportunity cost of better fuel efficiency at all quality levels. Total annual opportunity costs of owning highly fuel efficient cars increase, while they decline for cars of low fuel efficiency. We further find that both a fuel tax and a kilometer charge reduce the total annual fixed ownership cost for car attributes that raise the variable cost of driving (engine power, acceleration speed, etc.). There is thus in general a trade-off between fixed and variable car costs: if the latter increase - due to higher fuel prices or a kilometer charge - total demand for cars decreases and a return to equilibrium is only possible by a decrease in fixed costs. All theoretical results are illustrated using a numerical version of the model. The analysis shows that modeling the effect of tax changes on household behavior alone can produce highly misleading results.
urn:NBN:nl:ui:31-1871/39444
Keywords: H22; L62; 330; car market; car quality; fuel tax; kilometer charge; market equilibrium; Benzinpreis; Mineralölsteuer; Steuerwirkung; Kraftfahrzeugtechnik; Technischer Fortschritt; Konsumentenverhalten; Kraftfahrzeug; Theorie; Welt